ESTIMATION OF RAINFALL EROSIVITY IN SOUTHWESTERN NIGERIA - AKINWUMI, F. T; OYEDELE, D. J.; TIJANI, F. O (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2022)
The study assessed rainfall erosivity in southwestern Nigeria and compared site-specific rainfall erosivities obtained from commonly used indices. Pre-calibrated automatic weather stations were installed at three different locations across the study area and programmed to log rainfall amounts at five minutes intervals. Recorded rainfall data were downloaded monthly from the weather stations. 30-minute and 7.5-minute maximum intensity as well as rainfall energy were calculated. The EI30 erosivity index was estimated as a product of rainfall energy and 30-minute maximum intensity while the AI7.5 erosivity index was determined as a product of 7.5-minute intensity and amount of rainfall for each rainfall event. Modified Fournier index (MFI) rainfall erosivity was also estimated. Statistical correlations were drawn between EI30 and AI7.5, and between El30 and MFI.. The EI30 distribution showed that rainfall in September 2012 was the most erosive (45988 MJmm ha hr mth) while AI7.5 indicated that October 2011 had the highest erosivity (2994.46 cm2/h) in Ile-Ife. There were positive significant correlations between EI30 and AI7.5. Positive significant correlations were also obtained between EI30 and MF. The study concluded that rainfall in the study area falls into the strong erosivity class. The EI30 and AI7.5 indices are, therefore, suitable for the estimation of rainfall erosivity in Southwestern Nigeria. Further investigation of the soil loss and monthly erosivities as they relate to temporal rainfall aggressiveness is recommended.